Mercury, copper, and zinc concentrations in extracted human teeth - Brigato, Rita de Cássia Villar; Costa, Liovando Marciano; Costa, Marcelo Rocha da; Assis, Neuza Maria Souza Picorelli; Kubo, Claudio Hideki [UNESP] (Taylor & Francis, 2009)
Amalgam has been used as a filling material for over 150 years. Mercury, copper, and zinc are present in restoration. The aim of this study was to compare mercury, copper, and zinc concentrations in extracted human teeth with amalgam restorations and teeth without restorations. Thirty-two teeth, 15 restored with dental amalgam and 17 without restorations, were chemically analyzed in an Optima 3300 DV (Perkin Elmer) plasma emission spectrometer. Mercury, copper, and zinc were found in human teeth regardless of the presence of amalgam restorations. The highest mercury concentrations were found in the coronary portions of the teeth with amalgam restorations. Copper concentrations were very high. Zinc concentrations in the teeth without restoration were lower than those seen in the coronary portion of the teeth with restorations. © 2009 Heldref Publications.
Keywords: Contamination; Heavy metals; Human teeth; copper; dental alloy; mercury; zinc; heavy metal; chemistry; human; tooth; canine tooth; chemical analysis; heavy metal poisoning; incisor; molar tooth; premolar tooth; priority journal; spectrometer; tooth extraction; tooth filling; Copper; Dental Amalgam; Humans; Mercury; Tooth; Zinc